The ZuoJinWan formula inhibits glycolysis of cisplatin resistant gastric cancer cells via p53 acetylation - Zan Li; Qiuxue Wu; Zhenzhen Wei; Yuli Zhang; Bin Han; Sailei Jia; Hua Sui; Qingfeng Tang (Elsevier, 2024)
Introduction: Gastric cancer is one of the common malignancies worldwide, and drug resistance is a major factor contributing to the difficulty of treatment in gastric cancer. Zuojinwan (ZJW) has been found to exhibit a certain inhibitory effect on tumor cells. However, the molecular mechanisms of ZJW reversing drug resistance in gastric cancer are still unclear. Method: Human gastric cancer cisplatin-resistant cells SGC-7901/DDP and BGC-823/DDP were divided into control groups, DDP groups (10 μg/mL), 2-DG (5 mM) groups, and ZJW (50 μg/mL) combined with DDP (10 μg/mL) groups. After 48 h of culture, cell proliferation inhibition rate, glucose uptake rate, ATP, and lactate production were detected. Following lentiviral transfection to overexpress GLUT1 and HDAC1, western blot analysis was employed to examine the expression of HDAC1, P53, Ace-p53, and glucose metabolism-related proteins such as GLUT1, LDHA, HK II in the cells. Results: The combination of ZJW and DDP significantly inhibits the proliferation and glycolysis of cisplatin resistant gastric cancer cells. Compared with the DDP group, the combination of ZJW and DDP exhibited a higher inhibition rate (P < 0.01), accompanied by a reduction in the expression of HDAC1 and P53 proteins. Conclusions: Zuojinwan can enhance the proliferation inhibition rate of SGC-7901/DDP and BGC-823/DDP cells, attenuate glycolysis, and reduce chemotherapy resistance. Its mechanism may be associated with the inhibition of HDAC1/P53 axis activity.